An enhanced learning approach for increasing student engagement, motivation and learning using gamification in blended teaching. (22nd January 2022) - Rajput, Pushpendra Kumar; Ravulakollu, Kiran Kumar; Singhal, Shailey
Modern education has allowed the growth of independent learning in all varieties of student communities. At times, student involvement in the learning process of a given course ceases to exist as it reaches the end. The objective of this research is to deploy gamification as a tool for increasing student engagement, motivation and thereby to observe the growth of their learning. The study explores the possibilities of dimensions in the form of game design elements. These elements an instructor can deploy in the teaching-learning process. Quantitative and qualitative analysis performed on two batches of students for successive two terms shows a significant improvement in terms of engagement, motivation and student learning.